Branching Off: New Insight Into Lysosomes as Tubular Organelles - Bohnert, K. Adam; Johnson, Alyssa E. (Frontiers in Cell and Developmental Biology, 2022)
Lysosomes are acidic, membrane-bound organelles that play essential roles in cellular quality control, metabolism, and signaling. The lysosomes of a cell are commonly depicted as vesicular organelles. Yet, lysosomes in fact show a high degree of ultrastructural heterogeneity. In some biological contexts, lysosome membranes naturally transform into tubular, non-vesicular morphologies. Though the purpose and regulation of tubular lysosomes has been historically understudied, emerging evidence suggests that tubular lysosomes may carry out unique activities, both degradative and non-degradative, that are critical to cell behavior, function, and viability. Here, we discuss recent advances in understanding the biological significance of tubular lysosomes in cellular physiology, and we highlight a growing number of examples that indicate the centrality of this special class of lysosomes to health and disease.